2021
DOI: 10.3389/fpsyg.2021.639225
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Norwegian Version of the Cognitive Therapy Adherence and Competence Scale (CTACS) and Its Associations With Outcomes Following Treatment in IAPT Norway

Abstract: Background: No studies have examined the underlying structure or predictive validity of the Cognitive Therapy Adherence and Competence Scale (CTACS). Examining the structure of the CTACS is of great relevance because it could provide information on what constitutes competence in CBT, and whether some underlying factors are more important for predicting treatment outcomes than others. This study investigates the psychometric properties of the Norwegian version of CTACS and its associations with treatment outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…This implies that either it was difficult to come to an agreement regarding these items, or there was something with the instrument that made it difficult to calibrate and reach consensus when scoring these items. As Lervik et al ( 2021 ) also suggests, it is probably more difficult to score and interpret interpersonal relationships and the more abstract items, as opposed to more structural and concrete parts of a CBT-intervention (e.g., checking homework assignments, or putting up an agenda). Although the scoring team discussed the content and meaning of each item all along, a thorough operationalization beforehand could have provided even more accurate assessments.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that either it was difficult to come to an agreement regarding these items, or there was something with the instrument that made it difficult to calibrate and reach consensus when scoring these items. As Lervik et al ( 2021 ) also suggests, it is probably more difficult to score and interpret interpersonal relationships and the more abstract items, as opposed to more structural and concrete parts of a CBT-intervention (e.g., checking homework assignments, or putting up an agenda). Although the scoring team discussed the content and meaning of each item all along, a thorough operationalization beforehand could have provided even more accurate assessments.…”
Section: Discussionmentioning
confidence: 99%
“…While the scale can measure both adherence and competence, this study only collected competence scores. According to the psychometric evaluation of the Norwegian version of the CTACS by Lervik et al (2021) there is no evidence for divergent validity between the adherence and competence scale. The study reported acceptable internal consistency for the full scale (α = 0.91) and acceptable to low internal consistency for the subscales structure (α = 0.76), therapeutic relationship (α = 0.84), and CBT techniques (α = 0.73) and conceptualization (α = 0.61).…”
Section: Methodsmentioning
confidence: 99%